Mechanical, and tribological properties of ti/tin bilayers: the dependence of ti interlayer thickness (2013)
Ti/TiN bilayers were grown on AISI 316L stainless steel and Dynasil (SiO2) substrates, by using a reactive DC magnetronsputtering system. The Ti interlayer was grown at different thicknesses (0, 50, 100, and 200 nm) in order to study their infl uence on themorphological, mechanical, and tribological properties of the bilayers. The coatings’ morphology was determined using an XP2 profi lometeradhesion was measured using micro-scratch test equipment, mechanical properties were obtained by a NANOVEA IBIS–Technologynanoindenter with the Oliver-Parr method. Tribological characterization was carried out with a CSEM tribometer, and wear coeffi cientwas obtained by the Archard law by relating the wear area (measured by profi lometry). Results present a decrease in the roughness as theinterlayer was added. A maximum hardness and elastic modulus of 22 and 310 GPa, respectively, were obtained. On the other hand, thesystem with an interlayer of 100 nm exhibited the highest adhesion with a critical load of 28 N. Moreover, the system with an interlayer of200 nm showed an improvement in the tribological behavior due to its great load capability, lower substrate defl ection, and low wear rate.